Association of previous injury and speed with running style and stride-to-stride fluctuations - Mann, R.; Malisoux, L.; Nührenbörger, C.; Urhausen, A.; Meijer, K.; Theisen, D. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Running-related injuries remain problematic among recreational runners. We evaluated the association between having sustained a recent running-related injury and speed, and the strike index (a measure of footstrike pattern, SI) and spatiotemporal parameters of running. Forty-four previously injured and 46 previously uninjured runners underwent treadmill running at 80%, 90%, 100%, 110%, and 120% of their preferred running speed. Participants wore a pressure insole device to measure SI, temporal parameters, and stride length (Slength) and stride frequency (Sfrequency) over 2-min intervals. Coefficient of variation and detrended fluctuation analysis provided information on stride-to-stride variability and correlative patterns. Linear mixed models were used to compare differences between groups and changes with speed. Previously injured runners displayed significantly higher stride-to-stride correlations of SI than controls (P = 0.046). As speed increased, SI, contact time (Tcontact), stride time (Tstride), and duty factor (DF) decreased (P < 0.001), whereas flight time (Tflight), Slength, and Sfrequency increased (P < 0.001). Stride-to-stride variability decreased significantly for SI, Tcontact, Tflight, and DF (P = 0.005), as did correlative patterns for Tcontact, Tstride, DF, Slength, and Sfrequency (P = 0.044). Previous running-related injury was associated with less stride-to-stride randomness of footstrike pattern. Overall, runners became more pronounced rearfoot strikers as running speed increased